Successful treatment of infertility in a female Sumatran orangutan Pongo abelii. Issue 2 (10th April 2017) - Maclachlan, Neil; Hunt, Gordon; Fowkes, Sarah; Frost, Melissa; Miller, John; Purcell‐Jones, Gari; Sullivan, Peter; Barbon, Alberto; Routh, Andrew; López, Francisco J.; Price, Eluned C.
Abstract : In 2011, a female Sumatran orangutan housed at Durrell Wildlife Conservation Trust became infertile following a massive antepartum hemorrhage in labor and the delivery of a stillborn infant. The placenta was infected with Pantoea sp. Hysterosalpingography (HSG) revealed blocked fallopian tubes, and pressurized fallopian tube perfusion was used to reverse the tubal occlusion. She subsequently conceived and following an intensive training program, we were able to measure umbilical artery waveform analysis for fetal well‐being and placental localization to exclude placenta previa, which could complicate pregnancy and lead to catastrophic hemorrhage. The female went on to deliver a healthy offspring. We suggest that these techniques should be considered for other infertile females in the global captive population.